ANALISIS REAKSI PASAR ATAS PERISTIWA PENGUMUMAN KEBIJAKAN HOLDING BUMN PERTAMBANGAN - Anggraini, Fani (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2018)
This study aims to identify the reaction of the market regarding the holding policy of stateowned mining companies. The market reaction is proxied with abnormal return and trading volume activity (TVA) on 4 events; they are when the President Joko Widodo announced the holding policy, when PP No 47 of 2017 was issued, when Rini Soemarno signed the assets transfer deeds, and during the extraordinary general meeting of stockholders by Antam Tbk, Timah Tbk, and Bukit Asam Tbk. Using of purposive sampling method, 30 mining companies were selected as the sample. This study uses one sample t-test with the observation period of 7 days for each event. The results show a positive market reaction, which can be seen from the positive abnormal return and significant TVA, during the announcement of the holding policy. During the issuance of PP No 47 of 2017, there is no market reaction through abnormal return, but a positive market reaction is measured by significant TVA. Positive abnormal return and significant TVA are also recorded during the asset transfer deeds signing and during the extraordinary general meeting of stockholders. Therefore, it can be concluded that some market players positively responded the holding policy of state-owned mining companies. Â Keywords: abnormal return, trading volume activity, holding policy, semi strong form market efficiency.